Working from home and its challenges for transformational and health-oriented leadership - Tautz, Dorothee Caroline; Schübbe, Katharina; Felfe, Jörg (Frontiers in Psychology, 2022)
The Covid-19 crisis forced many employees to abruptly relocate their workplace from the office to their homes. As working from home is expected to remain part of our working world, consequences for leadership need to be examined. Our study aims to investigate the concrete challenges regarding the feasibility of transformational leadership and health-oriented leadership in this remote setting. Therefore, we collected quantitative and qualitative data of 23 leaders and 18 employees from various organizations in Germany. Both groups were asked to report their experiences during working from home in comparison to the traditional office setting. Findings of our study provide a comprehensive understanding regarding the underlying mechanism that impede transformational and health-oriented leadership in the remote setting. Among them participants reported a lack of social presence, limited informal chats, communication difficulties and lack of mutual trust. Based on our findings we derive practical implications for leaders and HR practitioners.